Identification of Pivotal Cellular Factors Involved in HPV‐Induced Dysplastic and Neoplastic Cervical Pathologies. Issue 4 (April 2014) - Mattarocci, Stefano; Abbruzzese, Claudia; Mileo, Anna M.; Carosi, Mariantonia; Pescarmona, Edoardo; Vico, Carmen; Federico, Antonio; Vizza, Enrico; Corrado, Giacomo; Arisi, Ivan; Felsani, Armando; Paggi, Marco G.
Abstract Cervical carcinoma represents the paradigm of virus‐induced cancers, where virtually all cervical cancers come from previous "high‐risk" HPV infection. The persistent expression of the HPV viral oncoproteins E6 and E7 is responsible for the reprogramming of fundamental cellular functions in the host cell, thus generating a noticeable, yet only partially explored, imbalance in protein molecular networks and cell signaling pathways. Eighty‐eight cellular factors, identified as HPV direct or surrogate targets, were chosen and monitored in a retrospective analysis for their mRNA expression in HPV‐induced cervical lesions, from dysplasia to cancer. Real‐time quantitative PCR (qPCR) was performed by using formalin‐fixed, paraffin embedded archival samples. Gene expression analysis identified 40 genes significantly modulated in LSIL, HSIL, and squamous cervical carcinoma. Interestingly, among these, the expression level of a panel of four genes, TOP2A, CTNNB1, PFKM, and GSN, was able to distinguish between normal tissues and cervical carcinomas. Immunohistochemistry was also done to assess protein expression of two genes among those up‐regulated during the transition between dysplasia and carcinoma, namely E2F1 and CDC25A, and their correlation with clinical parameters. Besides the possibility of significantly enhancing the use of some of these factors in diagnostic or prognostic procedures, these data clearly outline specific pathways, and thus key biological processes, altered in cervical dysplasia and carcinoma. Deeper insight on how these molecular mechanisms work may help widen the spectrum of novel innovative approaches to these virus‐induced cell pathologies. J. Cell. Physiol. 229: 463–470, 2014. © 2013 Wiley Periodicals, Inc.